Segmental cytomegalovirus colitis mimicking sigmoid tumor in an immunocompetent patient - Santacruz, Carlos Cerdán; Carlin, Patricia Sáez; Rancaño, Rocío Santos; Medina, Luis Ortega; Miguel, Javier Cerdán (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Cerdán Santacruz C, Sáez Carlin P, Santos Rancaño R, Ortega Medina L, Cerdán Miguel J. Segmental cytomegalovirus colitis mimicking sigmoid tumor in an immunocompetent patient. Turk J Gastroenterol 2019; 30(10): 932-4.